Protective coating for gabion wires against weathering elements and site conditions - Keong, Tan Kok; Chee Ming, Chan; Abdul Rashid, Azrin Hani (Penerbit Uthm, 2018)
Gabions are one of the most essential elements in the geotechnical field for their versatility and strength in slope stabilization. According to BS 8002:2015, gabions are rectangular large cages or baskets made of either steel wire or square welded mesh, and are usually filled with stones. Besides slope stabilization, gabions have been widely used for various purposes, including closing of river banks, road construction, landslide consolidation and hilly terrain reclamation [1].